2017
DOI: 10.1155/2017/7896160
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Preventing Endoscopic Recurrence of Crohn’s Disease 1 Year after Surgery: A Network Meta-Analysis

Abstract: Objective To assess the benefits of different treatments that aim to prevent the endoscopic recurrence of Crohn's disease (CD) after ileal resection. Methods Randomized controlled trials (RCTs) were searched from MEDLINE, Embase, and the Cochrane Central Database. All the included RCTs with an endoscopic recurrence outcome which was defined as Rutgeerts' score ≥ i2 have a duration of more than 1 year. The quality of the included RCTs was assessed by the Cochrane Risk of Bias Tool. Pairwise treatment effects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Recent studies suggest that submucosal lymphocytic plexitis in the proximal surgical margin is a predictor for endoscopic and clinical recurrence after ileocolonic resection, 32‐34 but more prospective research is necessary to verify this. We found that the prophylactic start of a maintenance treatment with anti‐TNF agents or thiopurines tended to decrease endoscopic recurrence after bowel resection, which is in line with a recent network meta‐analysis concluding that anti‐TNF drugs are superior to placebo or non‐biologic agents (budesonide, azathioprine or mesalazine) in preventing the endoscopic recurrence of CD, defined as Rutgeerts’ score of ≥i2, 1 year after ileal resection 35 . To date, there are not enough data on vedolizumab or ustekinumab in this context.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies suggest that submucosal lymphocytic plexitis in the proximal surgical margin is a predictor for endoscopic and clinical recurrence after ileocolonic resection, 32‐34 but more prospective research is necessary to verify this. We found that the prophylactic start of a maintenance treatment with anti‐TNF agents or thiopurines tended to decrease endoscopic recurrence after bowel resection, which is in line with a recent network meta‐analysis concluding that anti‐TNF drugs are superior to placebo or non‐biologic agents (budesonide, azathioprine or mesalazine) in preventing the endoscopic recurrence of CD, defined as Rutgeerts’ score of ≥i2, 1 year after ileal resection 35 . To date, there are not enough data on vedolizumab or ustekinumab in this context.…”
Section: Discussionsupporting
confidence: 88%
“…Available data suggest that certain drugs may reduce the likelihood of disease recurrence following the surgery; however, most studies discuss the risk of recurrence of endoscopic lesions rather than of clinical symptoms [ 270 ]. For example, the post-hoc analysis of the TOPPIC study revealed that 6-mercaptopurine increases the likelihood of complete mucosal remission (Rutgeerts score of i0) in smoking patients [ 271 ].…”
Section: Other Recommendationsmentioning
confidence: 99%
“…A total of 11 reviews related to cancer were identified, including NMAs of interventions for gastrointestinal cancer, pancreatic cancer, acute promyelocytic leukemia non-small cell lung cancer, neurotoxicity from chemotherapy, and cancer-related fatigue [37,54,66,74,82,89,95,105,107,112,113]. Osteoarthritis (including prostatitis) was the subject of 10 reviews [28-30, 40, 42, 73, 78, 101, 103, 114], gastrointestinal infections/disorders were the subject of 6 reviews [61,64,65,67,68,115], cardiovascular disease in 4 reviews [46,69,99,102], topics related to pregnancy, childbirth and newborn health in 4 reviews [47,62,71,83], and a variety of other clinical indications were assessed in 3 or fewer reviews. The number of NMAs overall increased notably from earlier to later years.…”
Section: Patient Indications and Outcomes Studiedmentioning
confidence: 99%